Comparison of QoS performance over WLAN, VoIP4 and VoIP6 - Musbah, Esra Musbah Mohammed; Bilal, Khalid Hamed; Mustafa, Nabi (International research journal of management, IT and social sciences, 2015)
VoIP stands for voice over internet protocol. It is one of the most widely used technologies. It enables users to send and transmit media over IP network. The transition from IPv4 to IPv6 provides many benefits for internet IPv6 is more efficient than IPv4. This paper presents a performance analysis of VoIP over WLAN using IPv4 and IPv6 and OPNET software program to simulate the protocols and to investigate the QoS parameters such as jitter, delay variation, packet send, and packet received and throughputs for IP4 and IP6 and compare between them.